Hubungan Status Gizi Lansia Dengan Angka Kejadian Asam Urat di Wilayah Kerja UPTD Puskesmas Sukaraya Tahun 2020 - Apria Wilinda Sumantri (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2021)
Hyperuricemia is a condition where there is an increase in blood uric acid levels above normal. In recent years, an increase in the prevalence of hyperuricemia and gout has been observed in epidemiological studies, and both diseases have become public health problems that need to be addressed as soon as possible.in general, the purpose of the research is to know it relationship of lansian nutrition status with uric acid event numbers in the working area puskesmas Sukaraya year 2020. This research includes research using quantitative correlation methods with a cross sectional approach and a sample size of 30 people. The variables studied are presented in the form of a frequency distribution table and tested with univariate and bivariate analysis, namely by using the demographic data questionnaire instrument, measuring the nutritional status of the elderly. The results of the study concluded that of the 30 respondents based on the frequency distribution, it was found that there were 0 (0%) respondents with normal nutrition who were exposed to ura acid and 15 (100%) respondents who were not exposed to gout. 10 (90.0%) respondents who were not affected by uric acid were 1 (9.1%) respondents, and out of 4 (100%) low nutrition respondents who were affected by gout were 4 (100%) respondents and those who not exposed to aric acid as much as 0 (100%) respondents. Based on the bivariate analysis, the p value was 0.000, meaning that there was a significant relationship with the nutritional status of lanisa and the incidence of gout. It is recommended that health workers check uric acid levels more frequently, especially for the elderly with a history of uric acid, so that the elderly can be more careful in choosing healthy food intake and normal nutrition.